Pengaruh Persepsi Kualitas Pelayanan, Kualitas Produk, dan Harga terhadap Loyalitas Pelanggan Flexi dengan Intervening Kepuasan Pelanggan - Suhaji, Suhaji; Sunandar, Haris (STIE Widya Manggala, 2010)
Technology development and operator increase as PT Telkom competitors make scope of market and customers fewer in number because of customers inloyalty. In accordance with this background, the research was made to find out the case of Flexi product’s decline. To maintain customers, we need to create our customer’s loyalty by improving our quality of service, quality of product and price. Improvement of those qualities and price will influence our customer’s satisfaction. And in the end, it will increase our customer’s loyalty.